Usefulness of focused screening echocardiography for collegiate athletes - Modaff, D. S.; Hegde, S. M.; Wyman, R. A.; Rahko, P. S. (The American Journal of Cardiology, 2018)
Sudden cardiac death in a young healthy athlete is a rare but catastrophic event. The American Heart Association preparticipation screening guidelines recommend a focused history and physical without routine imaging or electrocardiogram screening. We hypothesized that a focused echocardiogram can identify structural abnormalities that may lead to sudden cardiac death in athletes, which might otherwise go undetected by history and physical. We retrospectively reviewed the charts of all incoming collegiate athletes at a single university from 2005 to 2013, all of whom had undergone a focused, 5-minute echocardiogram along with a guideline-based preparticipation history and physical (PPS H&P). Abnormal findings prompted further testing or referral. We report the prevalence of abnormal findings and the relation between an abnormal PPS H&P and screening echocardiogram. A total of 2,898 athletes were screened and 159 (5%) had findings. Forty athletes underwent further testing and evaluation. Of these athletes, 3 had newly diagnosed abnormalities that warranted restriction of participation: 1 apical-variant hypertrophic cardiomyopathy, 1 large bidirectional atrial septal defect with right ventricular dysfunction, and 1 dilated ascending aorta. Two of these athletes had a normal PPS H&P. Conversely, of the 661 athletes with an abnormal PPS H&P, only 1 (0.15%) had an abnormal screening echocardiogram. In conclusion, although the overall number was low, the 5-minute screening echocardiogram detected athletes at risk for sudden cardiac death not discovered on PPS H&P.